On the verge of nuclear war: Global security challenges and dynamics in maintaining world peace - Alradix Djansena; Faisal Yusman; Heriyanta Sembiring; I Nyoman Parwata; I Wayan Midhio; Purnomo Yusgiantoro; Roedy Roedy; Trias Wijanarko; Yuli Kartiningsih (Goodwood Publishing, 2025)
Purpose: This research aims to identify the most effective strategies for maintaining world peace in the midst of these threats. The research methodology employs a hybrid approach, utilizing both the Analytic Hierarchy Process (AHP) and surveys. Research methodology: The survey involved 60 respondents from academia, policymakers, and the public to understand their perceptions of nuclear threats and mitigation strategies. This study is based on the theory of international system stability, which emphasizes the importance of multilateral cooperation and arms control. Results: The findings indicate that the most effective strategy is international diplomacy, with alliance strengthening and defense modernization following closely. We identify geopolitical threats, particularly unilateral actions, as major risk factors and emphasize that controlling the spread of nuclear technology is more significant than disarmament. These findings emphasize the need for a multidimensional approach based on diplomacy, technology control, and multilateral cooperation to create sustainable world peace. Conclusions: International diplomacy is the most effective strategy to maintain world peace amid nuclear threats, supported by nuclear technology control and strategic alliances through a multidimensional, cooperative approach. Limitations: The study's findings are limited by a small, region-specific sample and potential subjectivity in the AHP and survey methods. Contribution: This study provides a strategic basis for global security policy in the face of increasingly complex nuclear challenges.